APPLICATION OF ETHNOPEDAGOGICAL MODULE IN NATURAL SCIENCES BASED ON LOCAL WISDOM TOWARDS LEARNING INDEPENDENCE IN THEMATIC LEARNING - Fatmi, Nuraini; Sakdiah, Halimatus; Alchalil, Alchalil; Fitriani, Henni (Phi: Jurnal Pendidikan Fisika dan Terapan, 2024)
This research aims to determine students' responses to the implementation of ethnopedagogical modules in science-based on local wisdom in thematic learning towards learning independence. The research was conducted at SD Negeri 1 Muara Satu, Lhokseumawe City. Field problems found that during the learning process in both elementary schools, thematic learning had not been linked with ethnopedagogy based on local wisdom. Consequently, students lacked learning independence at school. The research type used was a pre-experimental design, labeled as such because it was not a full-fledged experimental study. The research design used was the One-Group Posttest Design, an experiment conducted with only one group without a comparison group. The sample in this study was a fifth-grade class with 114 students, selected using purposive sampling technique. This instrument aimed to assess students' learning independence after using the teaching module. The research results indicate that the implementation of the Ethnopedagogical Module, which smoothly integrates local wisdom and cultural contexts into science education, results in enthusiastic student engagement and contextualized learning experiences. This is evidenced by the results of the student learning independence test indicators, with the highest scores found in the research results for the learning independence variable in the indicator of having a competitive drive to advance. The overall sample obtained an average score of 83.2 in the category of excellent.